Manual of clinical microbiology - Jorgensen, James H(editor) (ASM Press, 2015)
The Gold Standard for medical microbiology, diagnostic microbiology, clinical microbiology, infectious diseases due to bacteria, viruses, fungi, parasites; laboratory and diagnostic techniques, sampling and testing, new diagnostic techniques and tools, molecular biology; antibiotics/ antivirals/ antifungals, drug resistance; individual organisms (bacteria, viruses, fungi, parasites).